Increasing preoperative cognitive reserve to prevent postoperative delirium and postoperative cognitive decline in cardiac surgical patients (INCORE): Study protocol for a randomized clinical trial on cognitive training - Butz, Marius; Meyer, Rolf; Gerriets, Tibo; Sammer, Gebhard; Doerr, Johanna M.; El-Shazly, Jasmin; Doeppner, Thorsten R.; Choi, Yeong-Hoon; Schoenburg, Markus; Juenemann, Martin (Frontiers in Neurology, 2022)
Introduction Postoperative delirium (POD) and postoperative cognitive decline (POCD) can be observed after cardiosurgical interventions. Taken together, these postoperative neurocognitive disorders (PNCDs) contribute to increased morbidity and mortality. Preoperative risk factors of PNCD, such as decreased neuropsychometric performance or decreased cognitive daily activities, can be interpreted as reduced cognitive reserve. This study aims to build up cognitive reserves to protect against the development of PNCD through preoperative, home-based, cognitive training. Methods The planned research project is a monocentric, two-arm randomized controlled intervention study involving 100 patients undergoing elective cardiac surgery with extracorporeal circulation. Patients will be assigned to a training group or control group. The intervention involves a standardized, paper-and-pencil-based cognitive training that will be performed by the patients at home for ~40 min per day over a preoperative period of 2–3 weeks. The control group will receive neither cognitive training nor a placebo intervention. A detailed assessment of psychological functions will be performed ~2–3 weeks before the start of training, at the end of the training, during hospitalization, at discharge from the acute clinic, and 3 months after surgery. The primary objective of this study is to investigate the interventional effect of preoperative cognitive training on the incidence of POD during the stay in the acute clinic, the incidence of POCD at the time of discharge from the acute clinic, and 3 months after surgery. Secondary objectives are to determine the training effect on objective cognitive functions before the surgery and subjective cognitive functions, as well as health-related quality of life 3 months after surgery. Discussion Should it become evident that the use of our cognitive training can both reduce the incidence of POCD and POD and improve health-related quality of life, this intervention may be integrated into a standardized prehabilitation program.